Compare The Efficacy of Transmasseteric Anteroparotid Approach with Conventional Retromandibular Transparotid - Nitesh Kumar (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The RM-A has been found to be superior to other methods due to its short access route, excellent visualization and access for reduction and fixation, quickness, and ability to achieve satisfactory aesthetic outcomes. Aim: To compare & assess the efficacy of T-AP for surgical MSCF-AP. Material & method: In our study we have performed T-AP–A using MSCF among 20-60 years patient in 2 differnt groups i.e. A & B. Result: We found that , group A showed significant difference for all the parameters from week 1 to 6 months as the p value was (0.00) for FN function & inter-incial and soalocele as the p value was 0.009. While for group B, showed not significant difference as the p value <0.05. Conclusion: The method is an effective for surgically treating fractures in the subcondylar area.